Nanotoxicology at the particle/micelle frontier: influence of core-polymerization on the intracellular distribution, cytotoxicity and genotoxicity of polydiacetylene micelles. Issue 4 (9th January 2020) - Costamagna, Federica; Hillaireau, Hervé; Vergnaud, Juliette; Clarisse, Damien; Jamgotchian, Lucie; Loreau, Olivier; Denis, Stéphanie; Gravel, Edmond; Doris, Eric; Fattal, Elias
Abstract : Non-polymerized micelles accumulate in the cell membrane inducing permeabilization and high toxicity; polymerized, particle-like micelles are internalized but exert low toxicity. Abstract : The understanding of the cellular uptake and the intracellular fate of nanoparticles and their subsequent influence on cell viability is challenging as far as micelles are concerned. Such systems are dynamic by nature, existing as unimers under their critical micelle concentration (CMC), and as micelles in equilibrium with unimers above the CMC, making canonical dose-response relationships difficult to establish. The purpose of this study was to investigate the in vitro cytotoxicity and uptake of two micellar sytems that are relevant for drug delivery. The two micelles incorporate a poly(ethylene glycol) coating and a pentacosadiynoic core which is either polymerized (pDA-PEG micelles) or non-polymerized (DA-PEG micelles), with the aim of evaluating the influence of the micelles status ("particle-like" or "dynamic", respectively) on their toxicological profile. Intracellular distribution and cytotoxicity of polymerized and non-polymerized micelles were investigated on RAW 264.7 macrophages in order to compare any different interactions with cells. Non-polymerized micelles showed significantly higher cytotoxicity than polymerized micelles, especially in terms of cell permeabilization, correlated to a higher accumulation in cell membranes. Other potential toxicity endpoints of polymerized micelles were then thoroughly studied in order to assess possible responses resulting from their endocytosis. No specific mechanisms of cytotoxicity were observed, neither in terms of apoptosis induction, cell membrane damage, release of inflammatory mediators nor genotoxicity. These data indicate that non-polymerized micelles accumulate in the cell membrane and induce cell membrane permeabilization, resulting in significant toxicity, whereas polymerized, stable micelles are internalized by cells but exert no or very low toxicity.